THU0233 Myopathy is a poor prognostic feature in systemic sclerosis. Results from the canadian scleroderma research group (CSRG) cohort. (23rd January 2014) - Jung, M.; Baron, M.; Hudson, M.; Bonner, A.; Pope, J.E.
Abstract : Background: Myopathy/myositis is associated with more severe systemic scleroderma (SSc). Objectives: The aim of this study was to determine such clinical information from the Canadian Scleroderma Research Group database (CSRG). Methods: Data from the CSRG are collected annually on SSc patients. Two surrogate markers for myopathy used in this study were elevated creatine kinase (CK) and physician-reported history of myopathy/myositis of the patients. Comparisons were made between those with and without myopathy/myositis to determine the strongest associations with this complication; overall, in lcSSc and dcSSc and in early dcSSc subset. Survival with and without myopathy/myositis was determined. Results: The study included 1143 patients with mean of 8 years of duration. Elevated CK occurred in 5.6%; 9.7% had a history of inflammatory myositis or myopathy according to physician; 5.7% had proximal muscle weakness. Those with elevated CK compared to remainder were more likely to be male (24.5% in elevated CK vs. 12.6% in normal CK; p<0.013), younger (51.93 vs. 56.07 years, p<0.045); have dcSSc, (40.4% vs. 37.9%; p<0.002), physician-reported history of myositis/myopathy (45.3% vs. 8.5%, p<0.000), tendon friction rubs (30.0% vs. 13.4%; p<0.001), FVC <70% (23.9% vs. 13.1%; p<0.039), RNP antibody (12.0% vs. 5.0%, p<0.032), Topo1 antibody (26.0% vs. 14.4%, p<0.026), higher skin scores (MRSS 16.14 vs. 9.81; p<0.000), and higher HAQ score (0.98 vs. 0.79; p<0.011). When using logistic regression younger age male, dcSSc, early dcSSc, tendon friction rubs, higher MRSS, Topo1, RNP, PMScl, and FVC<70% were associated with elevated CK. Survival was less in those with myopathy/myositis or elevated CK (p=0.003 and p=0.025 respectively). Those with elevated CK had less survival (p=0.025). Results were similar when the other definition of myopathy/myositis. Conclusions: Myopathy/myositis has a worse prognosis with respect to function and other organ involvement (ILD) and survival. Disclosure of Interest: M. Jung: None Declared, M. Baron: None Declared, M. Hudson: None Declared, A. Bonner: None Declared, J. Pope Grant/Research support from: Research support from CIHR, Scleroderma Society of Canada, Scleroderma Society of Ontario